Book review on Workgroups e-assessment: planning, implementing and analyzing frameworks - Li Liang (Journal of China Computer-Assisted Language Learning)
This review includes a brief description of the concepts of collaboration and assessment, an introduction to e-assessment approaches, a range of digital tools and their applications, and an explanation of underlying paradigms and theoretical frameworks, followed by a critical evaluation of the values and merits as well as the weak points of the book in question. The paper is intended to shed light on a new era of language educational assessment and provide reference points for relevant studies.